Parasitization and Identification of The Red Guava Fruit Fly Parasitoids in The Deli Serdang District - Sari, Putri Mustika; Bakti, Darma; Lisdayani, Lisdayani (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2019)
Deli Serdang District is one of the regions producing red guava fruit in Sumatra Utara. Cultivation of fruit trees is never separated from pest disorders, which can cause a decrease in the quality and quantity of fruit. Then proper control is needed so that it can maintain the balance of insect populations in the field. This study aims to determine the type of parasitoid and parasitoid parasitic levels in red guava crops. Identification morphology of parasitoid’s fruit flies rearing from red guava fruit that had been attacked by fruit flies was taken from several locations of red guava crops in Deli Serdang District. Two species of parasitoid Psytalia sp. the parasitic fruit fly in the red guava crop. The parasitoids that have been found then identified at LIPI, Cibinong, Bogor morphologically has many similarities with Psytalia walker and Psytalia walkeri so that identification of species is only made close to the morphology of the species. Only in two locations were found parasitoid’s rearing from infected fruit, namely Parasitization rate of 6.9% in Sei Beras Sekata village, and Kolam village of 3.6%.